Productivity Analysis And Engineering Of Oil Palm Factory Productivity Process On Boiler Work Effectiveness At PTPN III PKS Sei Mangkei - Alfrieldo Josua Sihombing (Journal Basic Science and Technology, 2021)
The boiler works to produce steam by heating the boiler water pipes..Boiler has a very important role in the continuity of performance of a Palm Oil Mill in other words can be said as the heart of the Palm Oil Mill,Boilers that have been used for a period of 20 years will certainly experience a decrease in performance, using the Overall Effectiveness Equipment (OEE) method we can know the value of Boiler Effectiveness, to get the OEE value we can see from the maintenance track record that has been carried out by the company, OEE Boiler Value in 2017 obtained average value is 39.08%, this is caused by the high the value of Reduced Speed ??Losses on the Analysis of Six Big Losses in Boiler Sei Mangkei Palm Oil Mill, which is 79.01%.